Pharm Adv 2021
DOI: 10.36118/pharmadvances.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the anticancer properties of quercetin

Abstract: Quercetin is a major constituent of various dietary products, which is increasingly being investigated as a therapeutic option in the oncological field. It has attracted extensive interest due to its ability of interacting with different molecular targets and evoking a broad spectrum of chemopreventive and anticancer activities. In this review, we have tried to present and critically discuss its potential against an extensive range of cancers including lung, ovarian, prostate, breast, colorectal, bladder cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…In other words, pharmacovigilance and pharmacosurveillance are very useful and essential tools to fi ne-tune therapies and provide indications for future research (2) Being a pharmacologist also means having broad views of human pathology and of the many molecules available to address health issues. In consonance with the mission of the recently-established IUPHAR Mediterranean Group of Natural Products Pharmacology -IMGNPP (and take note that on Feb 24-26/2022 Naples, Italy, will host the Joint meeting on Natural Products Pharmacology -SIF -SIPHAR -IMGNPP), two papers review the pharmacological properties of (poly)phenols, namely flavonoids (11) and quercetin (12). Even if often viewed as mere herbal substances, these molecules have a broad spectrum of action and could and should be studied in details, including human trials.…”
mentioning
confidence: 87%
“…In other words, pharmacovigilance and pharmacosurveillance are very useful and essential tools to fi ne-tune therapies and provide indications for future research (2) Being a pharmacologist also means having broad views of human pathology and of the many molecules available to address health issues. In consonance with the mission of the recently-established IUPHAR Mediterranean Group of Natural Products Pharmacology -IMGNPP (and take note that on Feb 24-26/2022 Naples, Italy, will host the Joint meeting on Natural Products Pharmacology -SIF -SIPHAR -IMGNPP), two papers review the pharmacological properties of (poly)phenols, namely flavonoids (11) and quercetin (12). Even if often viewed as mere herbal substances, these molecules have a broad spectrum of action and could and should be studied in details, including human trials.…”
mentioning
confidence: 87%
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…These interesting properties are also exploited in clinical settings, mainly in the aromatherapy [103,104]. Regarding cancer, which is characterized by an uncontrolled cell proliferation and a disrupted cell cycle, leading to aberrant cells that infiltrate and metastasize to other regions of the body, flavonoid act by a wide plethora of mechanisms [105][106][107][108]. Moreover, it was documented that these compounds are able to counteract not only genetic causes of cancer development [109], but also external causes, such as pollution, smoking or radiation [110].…”
Section: Flavonoids: Mechanisms Of Action In Cancermentioning
confidence: 99%